STRATEGI PENINGKATAN SUMBER DAYA MANUSIA PELAKU UMKM DESA MELALUI OPTIMASI PLATFORM DIGITAL DALAM ASPEK PRODUKSI, PEMASARAN DAN PERMODALAN - Chaerul Rizky; Yohny Anwar; Noni Ardian; Roisayudha Pradhana Suharsono (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2024)
This community service activity was carried out in Pematang Serai Village with the aim of increasing the human resource capacity of village MSMEs through optimizing digital platforms. The activity participants consisted of 50 local MSME actors operating in various business sectors. This program focuses on three main aspects: production, marketing, and capital. In the production aspect, participants are trained to use cloud-based inventory management and quality control applications to increase efficiency. In the marketing aspect, MSME players are introduced to digital marketing strategies through social media and e-commerce, with a target of increasing online sales by 30% in 6 months. Meanwhile, for the capital aspect, participants were taught to access fintech and crowdfunding services, with the result that 40% of participants succeeded in getting additional capital through digital platforms. The methods used include lectures, simulations and individual mentoring. The long-term impact of this activity is expected to increase the competitiveness and economic independence of MSMEs in Pematang Serai Village, as well as strengthening the local economy through the development of more modern businesses integrated with digital technology.